Teachers' Learning act which Develop the Students' Creativity - Moh. Irtadji (Universitas Negeri Malang, 2015)
Tindak Pembelajaran Guru yang Menumbuhkembangkan Kreativitas Siswa Abstract: The focus of this research is how the action of teachers learning that increase creativity of students. Research using qualitative approach, the type of basic or generic. The results showed that the form action of teacher learning fosters student creativity is creating an environment of psychologi-cal safety and free learning by using a variety of learning methods. Form of action teacher is giving acceptance and trust, provide challenges, provides an opportunity to express and appreciate feelings and thoughts, giving free rein to initiative and work to students. Key Words: action of teacher learning , students' creativity, elementary school Abstrak : Fokus penelitian ini adalah bagaimana tindak pembelajaran guru yang menumbuhkembang-kan kreativitas siswa. Penelitian menggunakan pendekatan kualitatif jenis basic or generic. Hasil pe-nelitian menunjukkan bahwa bentuk tindak pembelajaran guru yang menumbuhkembangkan kreativi-tas siswa adalah menciptakan lingkungan psikologis pembelajaran yang aman dan bebas dengan menggunakan beraneka ragam metode pembelajaran. Bentuk tindakan guru adalah memberikan peneri-maan dan kepercayaan, memberikan tantangan, memberikan kesempatan mengekspresikan dan menga-presiasi perasaan dan pikiran, memberi kebebasan untuk berprakarsa dan berkarya kepada siswa. Kata kunci : tindak pembelajaran guru,  kreativitas siswa, sekolah dasar